The principle of contractual security in european private law and its implementation in civil legislation of Ukraine - Суха, Юлія Сергіївна; Сухая, Юлия Сергеевна; Sukha, Yulia S. (My University, 2015)
Стаття присвячена дослідженню одного з базових основоположних принципів проекту DCFR – принципу договірної безпеки. Розкривається зміст даного принципу у відповідності до авторського бачення розробників DCFR, встановлюється значення складових принципу договірної безпеки. Аналізується стан впровадження зазначеного принципу у чинному цивільному законодавстві України, зокрема, у Цивільному кодексі України.

Статья посвящена исследованию одного из базовых основополагающих принципов проекта DCFR – принципа договорной безопасности. Раскрывается содержание данного принципа в соответствии с авторским видением разработчиков DCFR, устанавливается значение составляющих принципа договорной безопасности. Анализируется состояние внедрения указанного принципа в действующем гражданском законодательстве Украины, в частности, в Гражданском кодексе Украины.

The article is devoted to review of one of the fundamental underlying principles of the project DCFR – the principle of contractual security. The content of this principle is disclosed in accordance with the author’s position of the DCFR’s developers. The meaning and importance of the components fixed to the principle of contractual security is stated. The status of implementation of this principle in the current civil legislation of Ukraine, including the Civil Code of Ukraine, is analyzed.
Sukha Yu. S. The principle of contractual security in european private law and its implementation in civil legislation of Ukraine / Yu. S. Sukha / Часопис цивілістики. – 2015. – Вип. 19. – С. 23-27.
Keywords: принципи приватного права; принципи договірного права; проект DCFR; договірна безпека; європейське приватне право; принципы частного права; принципы договорного права; проект DCFR; договорная безопасность; европейское частное право; principles of private law; principles of contract law; project DCFR; contract security; European private law